Case Report: Combined Small Cell Lung Carcinoma With Pulmonary Adenocarcinoma - Shen, Cheng; Che, Guowei (Frontiers in Surgery, 2022)
Background Combined small cell lung carcinoma is defined as cancer tissues that mainly contain small cell lung cancer (SCLC) components with non-SCLC (NSCLC) histopathological types. The most common part of NSCLC is squamous cell carcinoma or large cell carcinoma. Combined SCLC (CSCLC) contains adenocarcinoma is extremely rare. Case Presentation We reported a case with surgically treated diagnosed as CSCLC with adenocarcinoma in an elderly and we summarized the clinical features of this disease. The patient has remained well for over 2 weeks after the treatment. Conclusion There are still few research reports on CSCLC. Since the survival time of patients with advanced CSCLC is shorter than that of simple SCLC, the recommended treatment for CSCLC is early detection and early surgery. In order to facilitate preoperative diagnosis and avoid misdiagnosis of such rare diseases, more cases need to be reported.